Incorporation of volcanic SO2 emissions in the Hemispheric CMAQ (H-CMAQ) version 5.2 modeling system and assessing their impacts on sulfate aerosol over the Northern Hemisphere - S. Itahashi; R. Mathur; C. Hogrefe; S. L. Napelenok; Y. Zhang (Geoscientific Model Development, 2021)
The state-of-the-science Community Multiscale Air Quality (CMAQ) Modeling System has recently been extended for hemispheric-scale modeling applications (referred to as H-CMAQ). In this study, satellite-constrained estimation of the degassing SO2 emissions from 50 volcanoes over the Northern Hemisphere is incorporated into H-CMAQ, and their impact on tropospheric sulfate aerosol (<msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="544235742d8f4a0f97153436b699bab8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00001.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00001.png"/></svg:svg>) levels is assessed for 2010. The volcanic degassing improves predictions of observations from the Acid Deposition Monitoring Network in East Asia (EANET), the United States Clean Air Status and Trends Network (CASTNET), and the United States Integrated Monitoring of Protected Visual Environments (IMPROVE). Over Asia, the increased <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="28cd4f8c12cf9ef751545712573a522a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00002.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00002.png"/></svg:svg> concentrations were seen to correspond to the locations of volcanoes, especially over Japan and Indonesia. Over the USA, the largest impacts that occurred over the central Pacific were caused by including the Hawaiian Kilauea volcano, while the impacts on the continental USA were limited to the western portion during summertime. The emissions of the Soufrière Hills volcano located on the island of Montserrat in the Caribbean Sea affected the southeastern USA during the winter season. The analysis at specific sites in Hawaii and Florida also confirmed improvements in regional performance for modeled <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="a8455a3a3390243c17ea2f3ca419ac4e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00003.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00003.png"/></svg:svg> by including volcanoes SO2 emissions. At the edge of the western USA, monthly averaged <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="40da026c69d6bb7b362f8aefb7758b92"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00004.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00004.png"/></svg:svg> enhancements greater than 0.1 µg m−3 were noted within the boundary layer (defined as surface to 750 hPa) during June–September. Investigating the change on <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="8c898138530c760447165fe6cdc920bb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00005.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00005.png"/></svg:svg> concentration throughout the free troposphere revealed that although the considered volcanic SO2 emissions occurred at or below the middle of free troposphere (500 hPa), compared to the simulation without the volcanic source, <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="97cb19aa5ca8b26a6d7fd7d4bad307d2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00006.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00006.png"/></svg:svg> enhancements of more than 10 % were detected up to the top of the free troposphere (250 hPa). Our model simulations and comparisons with measurements across the Northern Hemisphere indicate that the degassing volcanic SO2 emissions are an important source and should be considered in air quality model simulations assessing background <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="14485914c781d9e26f0da54782d5723d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-5751-2021-ie00007.svg" width="29pt" height="17pt" src="gmd-14-5751-2021-ie00007.png"/></svg:svg> levels and their source attribution.